2016
DOI: 10.4037/ajcc2016219
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Importance of Sleep Quality in Patients With Heart Failure

Abstract: Impaired sleep quality was prevalent in patients with heart failure and was associated with poor cardiac event-free survival. Clinicians should assess and manage sleep quality in patients with heart failure to improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
52
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 44 publications
7
52
3
1
Order By: Relevance
“…[33] Moreover, anxiety, appetite and sleep were confirmed to be predictors of readmission for CHF in retrospective studies, which may have been impacted by the fact that the patient's status influences the risk of readmission. [34][35][36][37] Kitamura M not only confirmed that daily activities were independent predictors of readmission in heart failure patients within 90 days, but also calculated the cut-off value by ROC curve [38] and the study have also proved that self-care and daily activities are the mediating factors of readmission of heart failure. [39] While Hochang Benjamin Lee et al emphasized that personality disorders as predictors of incident cardiovascular disease increased risk disease, [40] our results are quite the opposite, which may be because the subjects studied were different; Apart from the results on patient paranoia, these findings were similar to the results of our reports on the readmission risk factors for CHF.…”
Section: Discussionmentioning
confidence: 74%
“…[33] Moreover, anxiety, appetite and sleep were confirmed to be predictors of readmission for CHF in retrospective studies, which may have been impacted by the fact that the patient's status influences the risk of readmission. [34][35][36][37] Kitamura M not only confirmed that daily activities were independent predictors of readmission in heart failure patients within 90 days, but also calculated the cut-off value by ROC curve [38] and the study have also proved that self-care and daily activities are the mediating factors of readmission of heart failure. [39] While Hochang Benjamin Lee et al emphasized that personality disorders as predictors of incident cardiovascular disease increased risk disease, [40] our results are quite the opposite, which may be because the subjects studied were different; Apart from the results on patient paranoia, these findings were similar to the results of our reports on the readmission risk factors for CHF.…”
Section: Discussionmentioning
confidence: 74%
“…Staniute et al further also demonstrated that anxiety, depression and social support can indirectly affect the quality of life of patients with HF [38]. Moreover, anxiety, appetite and sleep were confirmed to be predictors of readmission for CHF in retrospective studies, which may have been impacted by the fact that the patient's status influences the risk of readmission [39][40][41][42]. Kitamura M not only confirmed that daily activities were independent predictors of readmission in heart failure patients within 90 days, but also calculated the cutoff value by ROC curve [43] and the study have also proved that self-care and daily activities are the mediating factors of readmission of heart failure [44].…”
Section: Discussionmentioning
confidence: 96%
“…For example, in patients with heart failure, 63% report poor sleep quality that is associated with reduced cardiac event-free survival. 29 In AF specifically, sleep quality is poor in 50% to 55% of patients. 12 , 30 , 31 In this exploratory study, we examined sleep quality among AF patients being treated with ablation and who then participated in a randomized rehabilitation trial.…”
Section: Discussionmentioning
confidence: 99%